2020
DOI: 10.3389/fchem.2020.580022
|View full text |Cite
|
Sign up to set email alerts
|

Efficient White Electrochemiluminescent Emission From Carbon Quantum Dot Films

Abstract: Carbon quantum dots (CQDs) were manufactured from citric acid and urea in a gram-scale synthesis with a controlled size range between 1. 5 and 23.8 nm. The size control was realized by varying volume of the precursor solution in a hydrothermal synthesis method. The prepared CQDs were investigated using electrochemiluminescence (ECL) spectroscopy at interfaces of their electrode films and electrolyte solution containing coreactants rather than conventional optoelectronic tests, providing an in-depth analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…To further investigate the inner filter effect, the optical band gaps (E g ) of carbon dots and Ni 2+ were estimated from Tauc plot (Figure 5e and f) [57] . The Tauc plot showed that the optical band gaps of carbon dots and Ni 2+ are 5.3 and 3.8 eV, respectively, which are close the literature values [58–59] . The larger optical band gap of carbon dots confirmed that the emission energy after energy absorption was sufficient to be absorbed by Ni 2+ (Figure 5g), which is in consistency with the overlapped carbon dot emission and Ni 2+ absorption in Figure 5d.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…To further investigate the inner filter effect, the optical band gaps (E g ) of carbon dots and Ni 2+ were estimated from Tauc plot (Figure 5e and f) [57] . The Tauc plot showed that the optical band gaps of carbon dots and Ni 2+ are 5.3 and 3.8 eV, respectively, which are close the literature values [58–59] . The larger optical band gap of carbon dots confirmed that the emission energy after energy absorption was sufficient to be absorbed by Ni 2+ (Figure 5g), which is in consistency with the overlapped carbon dot emission and Ni 2+ absorption in Figure 5d.…”
Section: Resultssupporting
confidence: 75%
“…[57] The Tauc plot showed that the optical band gaps of carbon dots and Ni 2 + are 5.3 and 3.8 eV, respectively, which are close the literature values. [58][59] The larger optical band gap of carbon dots confirmed that the emission energy after energy absorption was sufficient to be absorbed by Ni 2 + (Figure 5g), which is in consistency with the overlapped carbon dot emission and Ni 2 + absorption in Figure 5d. Moreover, we believed that the functional groups of carbon dots, such as carbonyl, hydroxyl, and carboxylate groups, induced Ni 2 + via electrostatic attraction leading to effective inner filter effect.…”
Section: Ni 2 + Ion Detectionsupporting
confidence: 80%
“…The CDs with visible spectral emission can be obtained through a one pot pyrolysis method by adjusting the precursor or reaction conditions. [6][7][8][9][10] Lin et al 11 developed a variety of colored uorescent CDs using different precursors, and differences in particle size and nitrogen content were proposed to result in red-shied emission. The emission wavelength of CDs changed from 426 to 603 nm by changing the precursors from (o-, m-, p-) phenylenediamine, and tricolour CDs were prepared.…”
Section: Introductionmentioning
confidence: 99%
“…Adsetts and Ding et al. performed a CQD size dependent study on the CQD film AIECL and interfacial properties to understand CQD emission mechanisms [48] . The CQD sample series featured a range of sizes from 1.5 to 23.8 nm where the smallest (1.5 nm) and largest (23.8 nm) CQDs were covered in detail and referred to as CQD3 and CQD4 in this subsection.…”
Section: Ecl Of Carbon Quantum Dot Filmsmentioning
confidence: 99%